The Problem of Participation (Methexis) in Plato’s Parmenides and Greater Hippias - Petuška, Virgilijus (Problemos, 2018)
[only abstract in English; full article and abstract in Lithuanian]The paper deals with the Platonic doctrine of participation (methexis) as it is presented in Plato’s dialogues Parmenides and Greater Hippias. It is argued that even though the dialogues have different themes and contexts, the arguments they contain regarding the methexis doctrine point to the connection of the problem with the Divided Line analogy in Plato’s Republic, and, more specifically, to the subdivision of dianoia and reasoning that proceeds to its conclusions with the help of images. The main thesis of the paper is that in these dialogues Plato meant to show that on the level of dianoia the methexis relation between Forms and particulars will always remain problematic because of the reliance on images necessary in this stage of reasoning.
Keywords: participation, Plato, Divided Line analogy, Parmenides, Greater Hippias